Emotional availability in mother-child and father-child interactions as predictors of child’s attachment representations in adoptive families - Almeida, Ana Susana (2022)
Emotional availability (EA) in parent-child interactions is associated with positive child outcomes, including attachment security. However, little is known about EA in adoptive families. This study investigated the associations between secure representations of attachment in adopted children and the adoptive parents’ EA. The participants (n = 75) included 26 mothers, 23 fathers, and 26 children who were aged 3 to 9 years. Children completed the Attachment Story Completion Task. Adult-child dyadic relationships were assessed using the EA® System. The results showed that the children’s and parents’ EA, age when adopted, and time elapsed since adoption were associated with more secure children’s attachment representations. Implications for family support and public policy are discussed.